Eficácia de um protocolo imuno-histoquímico para detecção de Leishmaniaem pacientes com diferentes formas clínicas de leishmaniose tegumentar - Fernanda Aragao Grassi Marques (2015)
American cutaneous leishmaniasis, is infectious disease in which the amastigotes of Leishmania protozoan infect the mononuclear phagocyte system cells and generate lesions in the skin and mucous membranes. The diagnosis are based on clinical and epidemiological evidence, but must be confirmed by demonstration of the parasite. Effective treatment should be initiated to shorten the course of the disease and avoid disfiguring injuries and sequelae. The objective was to test the eficicácia of immunohistochemical diagnostic method that uses dog serum naturally infected with Leishmania Infantum chagasi as primary antibody. The method has been already standardized and was effective in previous work performed on patients in the city of Caratinga , Minas Gerais. Through collaborations, 75 patient samples were analyzed in eight states of the federation, all the tested samples had positive PCR for Leishmania. Most of the patients were men, aged 31 to 45, rural workers. Positivity were observed in the procedure in 69.30 % of the cases. There was no significant corrrelação between clinical forms, histological features, presence of necrosis, progression of the disease and positivity in the proposed technique. There were more positive cases in immunohistochemistry in patients with negative Montenegro skin test (P = 0.0474 ). We conclude that the immunohistochemical technique tested is effective in diagnosing ATL, has easy implementation and low cost.